Experimental Verification of the Field Robotic System for Pipeline Maintenance - Thanh Phuong Nguyen; Hung Nguyen; Nhat Minh Ngo; Ha Quang Thinh Ngo (IEEE Access)
In the domain of field robotic system, it must deal with several challenges during both design and development durations. This study aims to investigate the whole design of robotic system for the internal inspection of tube. Firstly, the robot configuration is launched to identify the physical dimensions. Owing to the size of tube and the curved trajectory, the estimated parameters and shape of robot could be known. Also, some thresholds are obtained in this design which allows the range of dimensions. Secondly, the kinematic robot is analyzed to compute the flexible motion. Through theoretical computations, its locomotion could be evaluated directly. To realize our design, thirdly the detailed selection of servo motor is introduced in order to provide the powerful drive. Hence, the result of driving computations is shown due to the practical specifications of motor. Correspondingly, the spring which plays a role as damper, is measured to suppress the required torques. This spring ensures the continuous contact between leg of robot and internal wall of tube. As a result of these evaluations, both computer-based model and real-world model have been experimented. To guarantee the effectiveness and feasibility of our approach, three levels of validations are presented. In the numerical simulation, the virtual environment is established to substantiate the robotic locomotion. For the laboratory validation, the hardware robot is confirmed the working abilities as well as some trial results. Lastly, this robot must be exemplified in the real scene such as factory or site construction. From these achievements, it could be obviously seen that our approach is proper and feasible for many applications.